Employees' intellectual property rights - Wolk, Sanna; Szkalej, Kacper (AIPPI law series ;, 2018)
In today's knowledge-based global economy, most inventions are made by employed persons through their employers' research and development activities. However, methods of establishing rights over an employee's intellectual property assets are relatively uncertain in the absence of international solutions. Given that increasingly more businesses establish entities in different countries and more employees co-operate across borders, it becomes essential for companies to be able to establish the conditions under which ownership subsists in intellectual property created in employment relationships in various countries. This comparative law publication describes and analyses employers' acquisition of employees' intellectual property rights, first in general and then in depth as manifested in 33 jurisdictions worldwide. The book was developed within the framework of the International Association for the Protection of Intellectual Property (AIPPI), a non-affiliated, non-profit organization dedicated to improving and promoting the protection of intellectual property at both national and international levels.